Strategi Pemasaran Media Sosial pada PT Cigwa Indonesia Jaya - Safira, Siti Nadya; Tjahja Andari, Titiek (Jurnal Riset Manajemen dan Akuntansi, 2026)
The development of social media has transformed tourism marketing communication into a more interactive and visually driven approach, requiring companies to adopt consistent content strategies to build brand image, expand reach, and enhance audience engagement. This Field Work Practice (KKL) report aims to identify and analyze the social media marketing strategies of PT Cigwa Indonesia Jaya (CIJ) in promoting the Cisarua Green World Adventure (CIGWA) destination, evaluate the development of engaging and relevant content, and examine the factors influencing its effectiveness. The methods employed include field observations, interviews, discussions with company representatives, as well as the analysis and implementation of marketing activities during the KKL period. The results indicate that CIJ’s social media management has not been optimal in terms of social presence, media richness, and self-disclosure, as reflected in low audience interaction, limited variation and depth of information in Instagram content, and a lack of authentic narratives such as visitor stories and testimonials. This condition is consistent with the 2024 revenue fluctuation, which averaged only 84% of the monthly target. The implications of these findings highlight the need to strengthen posting consistency, utilize interactive features (such as live sessions and polls), improve the quality of video/reels/infographic content, and implement storytelling based on visitor experiences and event (festival) activities to sustainably enhance engagement, loyalty, positive brand image, and revenue stability.